A qualitative study: experiences of stigma by people with mental health problems. (18th January 2018) - Huggett, Charlotte; Birtel, Michèle D.; Awenat, Yvonne F.; Fleming, Paul; Wilkes, Sophie; Williams, Shirley; Haddock, Gillian
Abstract : Objectives: Prior research has examined various components involved in the impact of public and internalized stigma on people with mental health problems. However, studies have not previously investigated the subjective experiences of mental health stigma by those affected in a non‐statutory treatment‐seeking population. Design: An in‐depth qualitative study was conducted using thematic analysis to investigate the experiences of stigma in people with mental health problems. Methods: Eligible participants were recruited through a local mental health charity in the North West of England. The topic of stigma was examined using two focus groups of thirteen people with experience of mental health problems and stigma. Results: Two main themes and five subthemes were identified. Participants believed that (1) the 'hierarchy of labels' has a profound cyclical impact on several levels of society: people who experience mental health problems, their friends and family, and institutional stigma. Furthermore, participants suggested (2) ways in which they have developed psychological resilience towards mental health stigma. Conclusions: It is essential to utilize the views and experiences gained in this study to aid understanding and, therefore, develop ways to reduce the negative impact of public and internal stigma. Practitioner points: People referred to their mental health diagnosis as a label and associated that label with stigmatizing views. Promote awareness and develop improved strategies (e.g., training) to tackle the cyclical impact of the 'hierarchy of labels' on people with mental health problems, their friends and family, and institutional stigma. Ensure the implementation of clinical guidelines in providing peer support to help people to combat feeling stigmatized. Talking about mental health in psychological therapy or health care professional training helped people to take control and develop psychological resilience.